Interval identification of structural parameters using interval overlap ratio and Monte Carlo simulation. (July 2018) - Deng, Zhongmin; Guo, Zhaopu
Highlights: A new strategy for interval identification of structural parameters is proposed. Accurate response intervals are obtained by use of MC simulation and surrogate models. Interval overlap ratio is constructed based on the concept of interval length. The proposed method has high precision in identifying intervals of input parameters. Abstract: In this paper, a new interval finite element (FE) model updating strategy is proposed for interval identification of structural parameters in the aspect of uncertainty propagation and uncertainty quantification. The accurate interval estimation of system responses can be efficiently obtained by application of Monte Carlo (MC) simulation combined with surrogate models. By means of the concept of interval length, a novel quantitative index named as interval overlap ratio (IOR) is constructed to characterize the agreement of interval distributions between analytical data and measured data. Two optimization problems are constructed and solved for estimating the nominal values and interval radii of uncertain structural parameters. Finally, the numerical and experimental case studies are given to illustrate the feasibility of the proposed method in the interval identification of structural parameters.